Surgical Indications for Proximal Limb Amputations in a Resource-limited Setting: A Single Institution’s Experience - Ja’Neil Grace-Marie Humphrey; Joseph Nthumba; Puja Jagasia; Peter M. Nthumba (Journal of Limb Lengthening & Reconstruction, 2025)
Introduction: Major limb amputations are among the most disabling surgical procedures currently performed. In particular, proximal limb amputations (PLAs) impose enormous functional and social challenges on patients and their families, as they leave minimal options for functional prostheses, especially in the low-resource settings. The authors report on the indications of a series of patients who underwent PLAs at a resource-limited hospital. Methods: Data from the hospital medical records and histopathology database of patients who underwent PLAs (forequarter, hindquarter amputations, or hip or shoulder disarticulations) at a hospital in a middle income country in the sub-Saharan African region over a 14-year period was retrospectively evaluated to determine the indications for surgical procedures and early outcomes. This article did not aim to assess the specific outcomes in this cohort, due to limited data. Results: A total 48 PLAs (nine forequarter amputations, five hemipelvectomies, and one shoulder and 18 hip disarticulations) were performed in 44 patients. The 27 males and 17 females had a mean age of 41 years. The most common indication was malignancy (63.6%) and the second most common was infection (16.8%). Conclusion: We assessed the indications for PLAs at our site, with the most common indication being malignancy. In addition to a lack of preventative screening for malignancy and effective infectious disease control, limited disability optimization and support in this community (ex . reliable prostheses) likely decrease surgical effectiveness. Therefore, PLA-associated risks in this cohort highlight the importance of early oncologic detection, infectious disease control, and chronic disease management in low-resource settings, where robust surgical outcome data are often unavailable.